Auditory brainstem response using psychological task in Autism Spectrum Disorder (ASD) children - Dzulkarnain, Ahmad Aidil Arafat; Shahrudin, Fatin Amira; Jamal, Fatin Nabilah; Rahmat, Sarah; Ahmad Basri, Nadzirah; Sidek, Shahrul Na'im; Md. Yusof, Hazlina; Khalid, Madihah (2021)
Background: Auditory brainstem response (ABR) can be influenced by cognitive task due to the sensory inhibition process known as auditory sensory gating. The ABR wave V amplitude has been reported to decrease with cognitive tasks compared to the standard ABR. Any abnormality in the ABR cognitive task may suggest a possibility of auditory sensory gating deficit. However, in the literature, ABR with cognitive tasks have only been conducted among the normal hearing population. Therefore, this study aims to investigate ABR using a psychological task in normally developing children and children with autism spectrum disorder (ASD). Methods: A total of 20 normally developing children and ASD children with normal hearing and middle ear function are expected to participate in this study. The ABR will be elicited using tone burst and narrow band LS CE Chirp stimuli at 1000 Hz (2-0-2 envelopes) using ipsilateral recording under condition 1 (without cognitive interference) and condition 2 (with cognitive interference). The cognitive interference will be elicited using a Stroop task procedure. The ABR wave V amplitude, latencies, total of correct response (cognitive task) and test reaction time will be measured and evaluated at 95% confidence intervals. Results: Two-way Repeated measure ANOVA will be used to analyze the ABR results within group (between test conditions) and between groups (normal versus ASD children). The results were hypothesized to show no changes in the ABR wave V amplitude from condition 1 (without cognitive interference) to condition 2 (with cognitive interference) in the ASD group. Conclusion: This study will provide a better understanding of the influence of cognitive interference in the ABR from the ASD population. A presence of abnormality in this study may suggest a possibility of auditory sensory gating deficit, especially in ASD children.